OVERVIEW OF THE STRENGTH OF THE FLOOR SLAB STRUCTURE WITH THE SAP 2000 APPLICATION - I Ketut Putra Adnyana; Masdiana Masdiana; Fitriah Fitriah (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2022)
In the Construction Work of the Kendari Mayor's Office Tower Building Where In Its Implementation There Are Many Work Items, One of which is Floor Plate Work. Where the Floor Plate is One of the Structural Components in building construction that has a role in a construction, especially building. In Planning The Floor Plate Is Planned To Have A Thickness Of 12 Cm And Use Bondelk Material ( Stell Deck ) And Wiremesh Which The Use Of This Material Is Chosen Because In The Implementation Process It Is Considered Faster And More Efficient. In the Floor Plate Planning Process, Softwere Auxiliary Structure is Used to Facilitate the Structure of the Floor Plate Which Is Ideal For Use In Construction. The purpose of this study is to be able to know and compare from two methods of planning the structure of the floor plate.namely, the calculation method manually or with the calculation method with the help of softewe strutkur, namely Sap 2000 and can find out from the two methods which method is more efficient in planning and can also describe the comparative results of the use of the two methods with the aim of determining the appropriate method for planning In the Field And Can To Do Floor Plate Structure Calculations, Especially Either With Manual Methods Or With The Help Of Softwere Structures. Keywords : Floor Plate, Stell Deck, Wiremesh, Sap 2000